2015
DOI: 10.4236/odem.2015.31001
|View full text |Cite
|
Sign up to set email alerts
|

Age, Race and Gender Spatiotemporal Disparities of COPD Emergency Room Visits in Houston, Texas

Abstract: Chronic obstructive pulmonary disease (COPD) is one of the major causes of morbidity and mortality in the United State. The investigation of the continuing increase in its prevalence and mortality has increased attempts to further understand its causes and how to manage it. Understanding the spatial and temporal distribution of COPD emergency room (ER) visits in Harris County (Houston) can guide these efforts in a uniform yet diverse setting like this one. The objectives of this study were to identify the temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Similar to CVD ER visits. COPD ER visits had positive significant associations with the being African American male, relative humidity, O3 of the same day, and PM2.5 of the same day [5]. Pair-wise correlations between the variables are given in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to CVD ER visits. COPD ER visits had positive significant associations with the being African American male, relative humidity, O3 of the same day, and PM2.5 of the same day [5]. Pair-wise correlations between the variables are given in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The persistent increase in CVD and COPD ER visits (Figure 3) in Houston, Texas could be attributed to variations in data coverage and completeness as well as socioeconomic factors including immigrations due to severe weather disasters where the majority of movers are usually those who belong to the traditionally under-served under-represented groups [5] [6]. The previous models were univariate, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of asthma-related mortality occurs in lower income countries [3] [4]. Research on environmental effects on asthma has demonstrated strong associations between asthma presentation and concentrations of criteria air pollutants: carbon monoxide (CO), nitrogen dioxide (NO 2 ), ozone (O 3 ), fine particulate matter (PM2.5), and sulfur dioxide (SO 2 ) [5]- [11]. Asthma symptoms include coughing, wheezing, chest tightness, and shortness of breath.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies focusing on the impact of socioeconomic status (SES) on asthma have demonstrated varying degrees of associations with factors like income, college education attainment, and living in urban or rural areas. These associations varied with demographic factors such as age and ethnicity [5] [7] [12] [13]. The effect of SES on asthma morbidity and mortality is attributed to factors such as living conditions, working environment, proximity to air pollutant discharge, and psychosomatic stress [7] [14].…”
Section: Introductionmentioning
confidence: 99%